Epoxy interlocking: A novel approach to enhance FRP-to-concrete bond behavior. (30th December 2018) - Jiang, Cheng; Wan, Baolin; Wu, Yu-Fei; Omboko, John
Highlights: A novel epoxy interlocking approach is proposed to enhance FRP-to-concrete bond. Partial interaction of epoxy interlocking was calibrated by test results. An analytical method was proposed to quantify partial interaction for epoxy ribs. A parametric study was conducted analytically on the effects of epoxy interlocking. Abstract: This paper presents a novel approach which can enhance the interfacial bond behavior between fiber reinforced polymer (FRP) composite material and concrete. Epoxy ribs are formed by grooving on the concrete surface before epoxy is applied. The dowel action from the epoxy ribs leads to an "epoxy interlocking" effect. The mechanism of the proposed epoxy interlocking approach was analyzed in this paper from both adhesion and interlocking aspects. Furthermore, the partial interaction of the epoxy interlocking was quantified and calibrated by experimental results. The epoxy interlocking in the tested specimens led to an 88.8% increase in bond strength on average. An analytical approach was proposed to quantify the average partial interaction for the individual epoxy ribs. The load-slip relationship for individual epoxy ribs was found to be related to concrete compression behavior. A parametric study was conducted analytically on the effects of groove depth and spacing, concrete strength and epoxy rib location. The reasonable results in the parametric study further verify the efficiency of the epoxy interlocking to enhance the bond performance between FRP and concrete.